CREATIVE, FUN, AND EFFECTIVE WRITING IN EFL CLASSROOMS - Irma Herawati; Tono Suwartono; Pipit Sri Mularsih (Prominent, 2022)
“Writing is difficult”. That might be the most common expression when the students are asked to make a writing composition, especially an English language composition. Actually, writing is a challenging activity not only for the students but also for the teacher. From the students’ point of view, writing is about finding the idea, organizing it, making sentences, and constructing them into coherent paragraphs or essay. Unfortunately, the students have lack of vocabulary to write and motivation in joining writing class. On the other side, the teacher is struggling with how to make the students able to find the ideas, then build them to make a good composition. The teacher must empower many kinds of media and also methods as well as techniques to make the writing class fun and effective. Hopefully, by practicing those suggested methods and techniques the students writing ability can be significantly improved.